2020
DOI: 10.3390/s20102770
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Closed-Loop Feedback Techniques in Sleep Studies—Related Issues and Future Directions

Abstract: Advances in computer processing technology have enabled researchers to analyze real-time brain activity and build real-time closed-loop paradigms. In many fields, the effectiveness of these closed-loop protocols has proven to be better than that of the simple open-loop paradigms. Recently, sleep studies have attracted much attention as one possible application of closed-loop paradigms. To date, several studies that used closed-loop paradigms have been reported in the sleep-related literature and recommend a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014;Choi, Kwon, & paradigms likely leads to many instances when stimulation is delivered during a suboptimal or even undesirable phase of the network oscillation. Arguably, this could influence the outcome of modulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014;Choi, Kwon, & paradigms likely leads to many instances when stimulation is delivered during a suboptimal or even undesirable phase of the network oscillation. Arguably, this could influence the outcome of modulation.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of non-invasive modulation of sleep oscillations has recently attracted significant attention (Bellesi, Riedner, Garcia-Molina, Cirelli, & Tononi, 2014; Choi, Kwon, & Jun, 2020; Fattinger et al, 2019; Frase et al, 2019; Geiser et al, 2020; Krugliakova et al, 2022; Malkani & Zee, 2020; Marshall, Helgadottir, Molle, & Born, 2006; Ngo, Martinetz, Born, & Molle, 2013; Schneider, Lewis, Koester, Born, & Ngo, 2020). Slow waves are a predominant type of sleep oscillatory activity during NREM sleep, but can also occur during REM sleep and wakefulness (Andrillon, Burns, Mackay, Windt, & Tsuchiya, 2021; Bernardi et al, 2019; Borbely, Tobler, & Hanagasioglu, 1984; Funk, Honjoh, Rodriguez, Cirelli, & Tononi, 2016; Vyazovskiy et al, 2014; Vyazovskiy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…49 Their similarity to slow oscillations (SO), which are supposed to be critically involved in memory consolidation, has provoked researchers to manipulate their occurrence with acoustic stimulation. Recently, Choi et al 50 51 This study demonstrated for the first time that this approach can be used to investigate sleep functions. One important conclusion, however, was that this effect critically depends on the prevailing brain state during presentation.…”
Section: Acoustic Stimulation During Sleep Sleep Improvementsmentioning
confidence: 86%
“…Namely, we train the model on subjects drawn only from phase 1 on the one hand, and on subjects drawn only from phase 2 on the other hand. The results of these experiments are presented in Table I, rows (8,9). We observe that the ANN trained on phase 1 performs almost as well as the ANN trained on the whole cohort (6) on all subsets, including phase 2, whereas the ANN trained on phase 2 is noticeably worse on all subsets, even including phase 2.…”
Section: ) Training and Evaluating On Different Phasesmentioning
confidence: 92%
“…The ability to interact with brain oscillations in a precisely-timed fashion to enhance or inhibit endogenous processes -using sensory [1], [2], [3], [4], electrical [5] or magnetic [6] stimulation -allows for their functional roles to be determined [7], and potentially for restoration of processes deteriorated by aging or pathology [8]. While there is a great deal of interest in closed-loop stimulation [7], [9], researchers lack flexible, powerful tools that are easily accessible. Research efforts are also limited by the portability of systems, and by their complexity and expense.…”
Section: Introductionmentioning
confidence: 99%